A Porter’s Five Forces Analysis of Mobile Phone Retail in Palu - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2025)
The rise of digital technologies has transformed the mobile phone retail landscape in Indonesia, particularly in regional cities such as Palu. This study investigates the competitive strategies employed by local smartphone retailers using Porter’s Five Forces framework. A qualitative case study methodology was applied, incorporating semi structured interviews, direct observations, and thematic analysis. Findings indicate that smartphones remain dominant despite emerging interest in substitute devices like smartwatches and tablets. Entry into the market is facilitated by e commerce and social media, although sustainability remains a challenge due to supply constraints and low profit margins. Supplier power is high, with retailers relying heavily on centralized distributors. Buyers exhibit increased price sensitivity and digital awareness, favoring promotions and flexible purchasing options. Competitive rivalry is marked by price competition and innovation in service delivery, particularly through social media marketing and after sales services. The study underscores the importance of strategic adaptability, customer engagement, and digital transformation in navigating a competitive retail environment. These findings offer empirical insight into localized market dynamics and provide recommendations for sustainable business practices among regional retailers. The research contributes to a broader understanding of how global strategic models can be adapted to emerging market contexts.